+0  
 
0
347
2
avatar+52 

Solve the equation.

 

(2x+6)^1/3 - (6x-1)^1/3 =0

 

Select the correct choice below and, if necessary, fill in the answer box to complete your choice.

 

A. the solution set is____.

B. There is no solution

 

 

Thank you in advance

yojaymarojas  May 14, 2017
edited by yojaymarojas  May 14, 2017
 #1
avatar+94134 
+1

Solve the equation.

 

(3x+4)^1/3 - (5x-1)^1/3 =0

 

\((3x+4)^{1/3} - (5x-1)^{1/3} =0\\ (3x+4)^{1/3} = (5x-1)^{1/3} \\ 3x+4=5x-1\\ 5=2x\\ x=2.5\)

Melody  May 14, 2017
 #2
avatar+92808 
+2

Just a slight error on Melody's part ....

 

(2x+6)^1/3 - (6x-1)^1/3 =0

 

Following the same procedure as Melody, we arrive at

 

2x + 6  =  6x - 1 

 

4x    =   7

 

x  =  7/4  =  1.75

 

 

cool cool cool

CPhill  May 14, 2017

15 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.